Colonic transendoscopic enteral tubing: A novel way of transplanting fecal microbiota - Peng, Zhaoyuan; Xiang, Jie; He, Zhi; Zhang, Ting; Xu, Lijuan; Cui, Bota; Li, Pan; Huang, Guangming; Ji, Guozhong; Nie, Yongzhan; Wu, Kaichun; Fan, Daiming; Zhang, Faming (Endoscopy International Open, 2016)
Background and study aims: Placement of a tube through the anus into the cecum has not yet been established as a method of administering whole-colonic treatment. The aim of this study was to evaluate the safety, feasibility, and value of transendoscopic enteral tubing (TET) for fecal microbiota transplantation (FMT) through the colon.Patients and methods: A prospective observational study was performed of FMT using a new colonic TET technique. Under endoscopic guidance, a TET tube was affixed to the cecum with clips. The safety, value, and satisfaction with the FMT by TET were evaluated.Results: A total of 54 patients underwent TET. The success rate of the TET procedure was 100 % (54/54). Duration of the TET procedures was 14.8 ± 5.8 min. During the TET tube retention period, 98.1 % (53/54) of patients were satisfied with TET. The retention time for whole-colon delivery of the fecal microbiota suspension was 12.4 ± 2.3 days. In 88.4 % (49/54) of cases, no discomfort was reported during injection through the TET tube of the microbiota suspension. No adverse events were see in patients who required tube extubation after FMT.Conclusions: Colonic TET is a novel, safe, convenient, and reliable procedure for FMT that results in a high degree of patient satisfaction.